Calyx and Corolla as Heliocaminiform Structures Enhance the Reproductive Adaptation of Brandisia hancei (Orobanchaceae) to Low Winter Temperatures - Yongquan Ren; Ruifeng Sun; Yu He; Xia Jiang; Weilai Chen; Hongyun Xu; Yanyan He; Xiaoling Tian (Ecology and Evolution)
ABSTRACT The thermoregulation of plants through the heliocaminiform effect of hollow structures is widespread but overlooked. Winter‐flowering plants in subtropical regions often suffer from low temperatures; however, the reproductive adaptations of these plants are not well understood. The functional advantages of persistent calyx and labiate corolla in Brandisia hancei were studied to clarify the mechanism of flower thermoregulation via heliocaminiform structures, and to understand the reproductive adaptation of floral temperature increases in winter. The daily dynamics of floral temperature were recorded under two weather conditions. Floral temperatures were also measured (1) under shaded conditions, (2) after calyx or corolla removal, and (3) after a hole was made or after the hole in the corolla was sealed. Seed production was then evaluated after perianth manipulation. The heliocaminiform effect of persistent calyx and labiate corolla was obvious under sunny conditions, and a maximum temperature excess up to 10°C was recorded. However, the temperature excess disappeared under overcast to rainy conditions or after shading. The removal of either the calyx or corolla generally reduced floral temperatures compared to intact flowers. Making a hole in the corolla also led to a slight decrease in floral temperature, which was partially restored after sealing the hole. Consistent with these thermal effects, the removal of the calyx and corolla even at later stages caused a reduction in seed production. Notably, making only a small hole in the corolla reduced seed production, whereas the number of seeds also rebounded after the hole was sealed. By effectively increasing floral temperature, the heliocaminiform effect of the calyx and corolla enhances the reproductive fitness of B. hancei. Our study presents empirical evidence for floral thermoregulation via heliocaminiform structures and for reproductive adaptation through floral temperature increases in winter conditions in subtropical regions.